2016
DOI: 10.1038/nchem.2566
|View full text |Cite
|
Sign up to set email alerts
|

Observation of trapped-hole diffusion on the surfaces of CdS nanorods

Abstract: In CdS nanocrystals, photoexcited holes rapidly become trapped at the particle surface. The dynamics of these trapped holes have profound consequences for the photophysics and photochemistry of these materials. Using a combination of transient absorption spectroscopy and theoretical modelling, we demonstrate that trapped holes in CdS nanorods are mobile and execute a random walk at room temperature. In CdS nanorods of non-uniform width, we observe the recombination of spatially separated electrons and trapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
261
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(289 citation statements)
references
References 49 publications
27
261
1
Order By: Relevance
“…We show that the rates are related to an anisotropic diffusion coefficient, and from the rate theory, propose a lower bound on the reorganization energy for hole hopping that is consistent with the experimental data reported in Ref. 26.…”
supporting
confidence: 90%
“…We show that the rates are related to an anisotropic diffusion coefficient, and from the rate theory, propose a lower bound on the reorganization energy for hole hopping that is consistent with the experimental data reported in Ref. 26.…”
supporting
confidence: 90%
“…Fort he unmodified CdSe NCs,t wo time constants, t 1 = 1.05 ps and t 2 = 34.6 ns,w ere needed for as atisfactory fit of the data. [14,15] This change is observed across all CdSe/PyAn complexes as the same functional group is involved. [14] Thet ime constants extracted are in good agreement with previous reports.…”
Section: Angewandte Chemiementioning
confidence: 88%
“…[14] Analysis of the ESA of the CdSe NC photosensitizers functionalized with pyridine bidentate ligands with at riexponential fit given the longest component fixed, yielded two other decay components with similar timescales of about 40 ps and approximately 1nsf or all three ligands.W en ote that the fastest decay process, t trap % 40 ps,isslower than that for the pristine CdSe NCs and may correspond to charge trapping to deeper defects that were created during ligand exchange and cleaning. [14,15] This change is observed across all CdSe/PyAn complexes as the same functional group is involved. In the presence of atransmitter ligand, the new decay constant, t q ,w ith at imescale of approximately 1ns, corresponds to an additional decay pathway introduced by surface-bound PyAn transmitters, which is most probably due to TET from F =AE 2("dark" state on NC) to T L1 (the triplet state on anthracene) or other decay processes induced by the disruption of the original ligand shell.…”
mentioning
confidence: 88%
“…Photoelectrochemical (PEC) water splitting offers a feasible approach for solar-to-hydrogen conversion to realize the utilization of solar energy, which is also one of the most promising strategies to solve the energy crisis. [6][7][8][9] The PEC application of CdS has been intensively studied. [3][4][5] As a narrow bandgap n-type semiconductor (2.4 eV), CdS has been widely studied as a typical PEC photoanode, owing to its visible-light absorption, high charge mobility, appropriate band position for water redox reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] As a narrow bandgap n-type semiconductor (2.4 eV), CdS has been widely studied as a typical PEC photoanode, owing to its visible-light absorption, high charge mobility, appropriate band position for water redox reaction. [6][7][8][9] The PEC application of CdS has been intensively studied. [10][11][12][13][14][15][16][17] However, many studies have revealed that the PEC activity of pure CdS is severely limited because of the highly photogenerated carrier recombination.…”
Section: Introductionmentioning
confidence: 99%